Innovative sanitation approaches to address multiple development challenges - Andersson, K.; Otoo, Miriam; Nolasco, M. (IWA Publishing, 2018)
Globally, more than 60% of the human population live without safely managed sanitation services or even lack access to basic sanitation facilities. In addition, most of the wastewater produced in the world is discharged without proper treatment. Integrated approaches are needed to address these issues and curb the resulting adverse impacts on public health and the environment, and associated societal economic losses. The UN 2030 SDG Agenda provides an important framework towards more sustainable sanitation development, in terms of both safe sanitation access and wastewater management. Innovative solutions that treat and enable productive safe use of water, and recovery of nutrients and organic matter from wastes resources are booming. Some examples of trends are decentralized solutions, separation of waste flows, low/or no-flushing toilets, and converting faecal sludge to energy. These alternative technologies show huge potential to address many development challenges, contributing to multiple SDGs, but achieving upscaling has proved to be a major challenge. A paradigm shift to ‘treatment for reuse’ instead of ‘treatment for disposal’ is already taking place in the wastewater sector. Nevertheless, a better understanding of driving forces and enabling environment, new organizational models based on more service-oriented sanitation provision, and highlighting potential multiple societal benefits to attract investments from new sectors, are identified areas that need further attention.